2020
DOI: 10.1002/mnfr.201901231
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Inhibits Autophagy and Induces Exosome‐Mediated Paracrine Senescence via Regulating mTOR/TFE3

Abstract: ScopeThe development of novel compounds that trigger non‐apoptotic cell death may represent alternative therapeutic strategies for esophageal squamous cell carcinoma (ESCC) treatment. Cellular senescence suppresses tumorigenesis by halting the proliferation of tumor cells, implying the induction of senescence as a promising anticancer strategy, especially when combined with senolytic agents that specially kill senescent cells. This study is designed to screen novel anti‐ESCC compounds from a natural product re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
4
32
0
Order By: Relevance
“…The complete protection of NAC from other SFN-induced cellular events, such as mitochondrial dysfunction, ERS, DNA damage, and autophagy, and the protection yielded by sodium pyruvate against impaired Δψ m collectively indicate an important role for ROS in these SFN-induced phenomena. The current findings are comparable to those of previous studies, in which SFN induced ROS-dependent Δψ m perturbations in human leukemia cells, 41 ROS-dependent DNA damage and responses in umbilical vein endothelial cells and esophageal cancer cells, 39 , 42 and ROS-dependent autophagy in colon, prostate, and esophageal cancer cells. 37 , 39 , 43 Moreover, although others have demonstrated the induction of ERS by SFN, 11 , 44 the current work provides the first evidence that the induction is ROS dependent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The complete protection of NAC from other SFN-induced cellular events, such as mitochondrial dysfunction, ERS, DNA damage, and autophagy, and the protection yielded by sodium pyruvate against impaired Δψ m collectively indicate an important role for ROS in these SFN-induced phenomena. The current findings are comparable to those of previous studies, in which SFN induced ROS-dependent Δψ m perturbations in human leukemia cells, 41 ROS-dependent DNA damage and responses in umbilical vein endothelial cells and esophageal cancer cells, 39 , 42 and ROS-dependent autophagy in colon, prostate, and esophageal cancer cells. 37 , 39 , 43 Moreover, although others have demonstrated the induction of ERS by SFN, 11 , 44 the current work provides the first evidence that the induction is ROS dependent.…”
Section: Discussionsupporting
confidence: 91%
“…In several cancer cell lines, SFN-induced cell cycle arrest or cell death was also prevented by alleviating ROS levels, such as by overexpressing catalase, an endogenous antioxidant, or supplementing cells with NAC or (2R, 4R)-4-aminopyrrolidine-2,4-dicarboxylate (ADPC), a ROS inhibitor. 23 , 36 39 The Nrf2 pathway regulates detoxification and antioxidant defense processes, and SFN is a potent activator of Nrf2. 4 Nonetheless, the elevation of Nrf2 activity beyond physiological levels can be detrimental to cells.…”
Section: Discussionmentioning
confidence: 99%
“…No publications are available dealing with the influence of SFN on Nrf2 in bladder cancer cells (where Nrf2 downregulation would be expected). SFN activated Nrf2 in normal esophageal epithelial cells, but not in esophageal cancer cells [ 128 ], which seems to be in accordance with the biphasic characteristics of SFN. However, inhibition of cell proliferation and invasion of pancreatic cancer cell lines by SFN was associated with translocation of Nrf2 from the cytoplasm into the nucleus [ 129 ].…”
Section: Sfn In Bladder Cancermentioning
confidence: 63%
“…A similar mode of action may hold true for SFN as well. In fact, induction of apoptosis and senescence of esophageal squamous cell carcinoma cells by SFN was triggered by a ROS-mediated mTOR inactivation [ 128 ].…”
Section: Sfn In Bladder Cancermentioning
confidence: 99%
“… 95 , 96 Zheng et al identified sulforaphane (SFN) could inhibit ESCC cell proliferation via inducing senescence. 97 Meanwhile, SFN caused autophagy dysfunction and exosome release in reactive oxygen species (ROS)-mammalian target of rapamycin (mTOR)-dependent manner participated in triggering paracrine senescence. The modulating autophagy and the exosome-mediated paracrine senescence represents a promising strategy for ESCC treatment.…”
Section: Utility Of Exosomes In the Treatment Of Ecmentioning
confidence: 99%